Application Development of Android Based for Monitor Prediabetic Self Care - Martini Listrikawati; Noor Fitriyani; Firman Prastiwi (GLOBAL HEALTH SCIENCE GROUP, 2024)
Diabetes occurs starting from the symptoms of prediabetes. Individuals with prediabetic conditions are more likely to develop Type-2 Diabetes mellitus 4 times greater than those with normal glucose tolerance. Intervention mobile app can be one of the solutions to increase awareness and compliance of intervention self-management of prediabetes state. There has been no research in the systematic review of intervention mobile phone applications to prevent the state of prediabetes. Objective: this study was to determine the behavior of prediabetes Self-Care in the Program Keluarga Harapan (PKH) group Method: The research method uses a cross-sectional approach. Results: respondents as many as 63 with the most age distribution of 26-35 years (31.7%) mostly female 73.1%, Education 84.1%. The results of the analysis of problems in the development of multimedia on Self-Care Prediabetes in the Hope Family Program group (PKH) for the risk of prediabetes into the category of moderate 36.5% and the results of self-care behavior prediabetes including bad category 57.1% Conclusions: Analysis of potential problems became the initial foothold in the development of smartphone-based self-care applications are still in the revision stage of the application media.